Computational optimization of cell culture media for cultured meat production - Chia, Shawn (Nanyang Technological University, 2024)
Alternative Proteins (AP), particularly Cultivated Meat (CM), offer a promising avenue towards sustainability by providing animal protein alternatives that require fewer resources and produce fewer negative externalities. This project presents a novel approach to identifying plant and fungal peptides as potential replacements for animal-derived growth factors in CM production. Through a computational screening prediction algorithm where peptides are encoded using the Quasi Sequence Order (QSO) effect to preserve the directionality of protein sequence descriptors, peptides from commonly cultivated plants and fungi were compared to growth factors from three targeted animal species: chicken, cow, and pig. The project identified four potential candidates: ITPK4_SOYBN (Inositol-tetrakisphosphate 1-kinase 4) from soybean for chicken growth factor replacement, A0A3B5Z4L3_WHEAT (Acireductone dioxygenase) from wheat for cow growth factor replacement, A0A3Q7F8S5_SOLLC (Peroxidase) from tomato for pig growth factor replacement, and GHD7_ORYSJ (Transcription factor GHD7) from rice as a replacement across targeted animal species. These peptides possess high sequence similarity to animal growth factors, suggesting their potential as non-animal alternatives for CM growth media. While further validation and refinement are required, this research lays the groundwork for leveraging plant and fungal resources to drive the development of sustainable food systems and to accelerate the commercialization of CM.